Beneficial effects of dietary copper supplementation on serum lipids and antioxidant defenses in rats - Galhardi, C. M.; Diniz, Y. S.; Rodrigues, H. G.; Faine, L. A.; Burneiko, R. C.; Ribas, B. O.; Novelli, ELB (Karger, 2005)
Background: A nutrition experiment was utilized to investigate the effects of two levels of dietary copper (Cu) supplementation on lipid profile and antioxidant defenses in serum of rats. Methods: Male Wistar rats (180-200 g; n = 10) were divided into three groups: control group (A), fed a basal diet with 6 mu g Cu/g, and rats fed a basal diet with Cu (CuSO4) supplementation from aqueous solutions, for 4 weeks at the final concentrations of 2 mg Cu/rat (B) and 3 mg Cu/rat (C). Results: No significant changes were observed in final body weight, body weight gain, food consumption, total serum protein and high-density lipoprotein. Cu supplementation reduced the triacylglycerol (TG), total cholesterol and low-density lipoprotein (LDL-C). The LDL-C/TG ratio and total antioxidant substances (TAS) were higher in (B) and (C) groups than in (A) group. There was a positive correlation between Cu supplementation and ceruloplasmin levels. The markers of oxidative stress, lipid hydroperoxide and lipoperoxide were decreased with Cu supplementation. No alterations were observed in superoxide dismutase, indicating saturation of Cu enzyme site. The glutathione peroxidase activities (GSH-Px) were increased in both Cu-supplemented groups. Considering that a copper-selenium interaction can affect mineral availability of both elements, the effects of Cu on TAS and GSH-Px activities were associated with increased selenium disposal. Conclusions: Dietary Cu supplementation had beneficial effects on lipid profile by improving endogenous antioxidant defenses and decreasing the oxidative stress in vivo. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: copper; lipid profile; oxidative stress; total antioxidant substances